A Typology for Aligning Organizational Ambidexterity's Conceptualizations, Antecedents, and Outcomes - Simsek, Zeki; Heavey, Ciaran; Veiga, John F.; Souder, David (Journal of management studies, 2009)
We take stock of the current body of knowledge and understanding on organizational ambidexterity to further specify the construct and develop a typology to focus this line of research. To that end, we first synthesize the various insights on ambidexterity's conceptualization in extant research. We then develop a parsimonious, yet coherent typology that delineates four archetypes of ambidexterity using two primary dimensions underlying previous conceptualizations of this construct. To help focus and align extant research, we next map these types onto the most salient theories, antecedents, and outcomes that are uniquely germane to each. Finally, we offer several recommendations and promising avenues for future inquiries that follow from our typology and associated discussion.